BIOLOGICAL-ACTIVITIES OF A TURKISH MEDICINAL PLANT, PRANGOS-PLATYCHLAENA - (:unkn) unknown (ELSEVIER SCI PUBL IRELAND LTD, 1995)
Prangos platychlaena has been used in traditional medicine in eastern Turkey. It stops bleeding and heals the scars when applied externally. When the isolated coumarins were tested against bacterial strains, only a slight activity was obtained.
Keywords: PRANGOS PLATYCHLAENA; UMBELLIFERAE; FOLK MEDICINE; ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES